To Compare the Effectiveness of Sustained Slow Stretch and Pressure Application in Spastic Diplegic Cerebral Palsy - Fazia, Banu; Prathap, Suganthirababu; Vinodhkumar, Ramalingam; Vignesh, Srinivasan; Kumaresan, Abathsagayam; Jagatheesan, Alagesan (INTI International University, 2023)
Background: The most common kind of cerebral palsy, which affects between 70 - 80 % of those diagnosed, is spastic cerebral palsy. Treatment options include surgery, medicine, and physical therapy. This illness impairs the coordination and regulation of motor function. In turn, the spinal cord's and the nerve’s responses are affected, resulting in the stiffness and spasticity of the muscles. The present study aimed to find the effectiveness of sustained slow stretch and pressure application in spastic diplegic cerebral palsy. Methodology: Based on inclusion and exclusion criteria, a comparative experimental study was carried on. 20 samples were divided into interventional (n=10) and conventional groups (n=10) and the samples were sampled according to convenient sampling. Interventional group received an inhibitory pressure application of about 35 to 50mmHg for 20 minutes with the help of sphygmomanometer over the hamstring muscle for 4 weeks. Conventional group received sustained slow stretch over the hamstring muscle for about 20 minutes per session for 4 weeks and the results will be interpreted. Results: There was only minor difference between the groups when compared statistically and was clinically significant. Conclusion: The result of this investigation allows us to draw the conclusion that both types of therapies, gradual continuous stretching and application of pressure, is effective.